Roma Victa - Lentzsch, Simon. author. aut Link
XII, 421 p. 1 illus.
Keywords: The history of the Roman Republic was a military success story. Texts, monuments and rituals commemorated Rome's victories, and this emphasis on its own triumphs formed a basis for the Roman nobility's claim to leadership. However, the Romans also suffered numerous heavy defeats during the Republic. This study is the first to comprehensively examine how Rome's defeats at the hands of the Celts, Samnites, and Carthaginians were explained and interpreted in the historical culture of the Republic and early imperial period. What emerges is a specifically Roman culture of dealing with defeats, which helped the Romans to find meaning in the stories of their failures and to assign them a place in their own past. Simon Lentzsch is a research assistant at the Chair of Ancient History at the University of Cologne. This book is a translation of an original German edition. The translation was done with the help of artificial intelligence(machine translation by the service DeepL.com). A subsequent human revision was done primarily in terms of content, so that the book will read stylistically differently from a conventional translation.